CHARACTER EDUCATION THROUGH CIVIC EDUCATION LEARNING IN ELEMENTARY SCHOOLS: A THEORETICAL AND EMPIRICAL LITERATURE ANALYSIS - Noviana , Irma; Mubarok , Husni (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
Character education is a fundamental pillar in shaping a generation that is virtuous, responsible, and patriotic. Civic Education (PPKn) learning in elementary schools plays a strategic role in internalizing character values in students from an early age. This study aims to theoretically and empirically analyze how Civic Education contributes to character formation among elementary-level students. Using a literature review method, the author examines various relevant scholarly works, including both theoretical perspectives and previous empirical findings. The results indicate that contextual approaches, value-based learning, and integration with the Pancasila Student Profile are effective strategies in fostering student character. Implementation challenges remain, particularly in terms of teacher competence and the readiness of educational resources. This review recommends strengthening the role of teachers and adopting a more flexible and contextual curriculum to ensure that Civic Education genuinely contributes to the holistic development of students’ character.